Integrated evaluation of external wall insulation in residential buildings using SWARA-TODIM MCDM method - Ruzgys, Audrius; Volvačiovas, Robertas; Ignatavičius, Česlovas; Turskis, Zenonas (Journal of Civil Engineering and Management, 2014)
A great part of energy produced in Europe is consumed by old residential buildings. Consequently, it is necessary to retrofit energetically non-efficient buildings. However, there is a mass financial gap between cost effective retrofitting and upgrading to nearly zero energy building levels. The efficiency of apartment building modernization under current requirements applicable in Lithuania and the requirements for 2020 was analysed, focusing on thermal insulation of external walls. Six cases of residential building modernization in Lithuania were studied estimating criteria that are among the most important for implementation of apartment building modernization, such as the total cost of the external wall modernization, simple payback period, work duration, and other parameters related to the characteristics of thermal insulation systems. The weights of the criteria were calculated after an expert survey and using integrated SWARA-TODIM multi-criteria decision-making (MCDM) method the best alternatives were ranked. After analyzing the differences between the current situation and upcoming requirements for rendered and ventilated type of façades, it can be stated that the final result depends more on price, duration of works, payback period, energy losses and water vapour diffusion than on the type of façade or insulation requirements applied at present or future.